Study on the influence of various base agents in K2TiF6 hydrolysis on morphology, structure and photocatalytic activity of TiO2 - Nguyen Tan Lam; Nguyen Thi Dieu Cam; Nguyen Phi Hung; Nguyen Van Noi (My University, 2017)
Study on the influence of various base agents in K2TiF6 hydrolysis on morphology, structure and photocatalytic activity of TiO2
Keywords: K2TiF6 hydrolysis; TiO2 morphology; Base agents